1994
DOI: 10.3109/10641969409067947
|View full text |Cite
|
Sign up to set email alerts
|

Carvedilol, A Novel Cardiovascular Agent, Inhibits Development of Vascular and Ventricular Hypertrophy in Spontaneously Hypertensive Rats

Abstract: The effects of carvedilol, a novel cardiovascular agent, were evaluated in developing spontaneously hypertensive rats (SHR) for effects on hemodynamics, and the ability to effect the development of left ventricular, and vascular hypertrophy associated with chronic hypertension. Chronic oral administration of low dose carvedilol (20 mg/kg/day) was initiated when rats were 5 weeks of age, and experiments progressed until 14 weeks of age. Carvedilol-treated SHR had significantly reduced systolic blood pressures a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 25 publications
2
12
0
Order By: Relevance
“…They also found that even though the blood pressure-reducing effect of the β adrenergic receptor blocker was less than that of the α1 blocker, the increase of heart weight was inhibited by the β Since left ventricular BNP mRNA expression by combination therapy with doxazosin and atenolol was significantly lower than that by atenolol monotherapy, the antihypertrophic effects may be enhanced when α1 and β adrenergic receptor antagonists are combined. Similarly, it has been reported that administration of carvedilol, which is an αβ adrenergic receptor antagonist, inhibits the development of cardiac hypertrophy in SHR (35). It has been indicated that α1 adrenergic receptor blockers reduce the unfavorable effect of β blockers on insulin sensitivity and lipid metabolism (36).…”
Section: Analysis Of Monotherapy and Combination Therapy Of Adrenergimentioning
confidence: 96%
“…They also found that even though the blood pressure-reducing effect of the β adrenergic receptor blocker was less than that of the α1 blocker, the increase of heart weight was inhibited by the β Since left ventricular BNP mRNA expression by combination therapy with doxazosin and atenolol was significantly lower than that by atenolol monotherapy, the antihypertrophic effects may be enhanced when α1 and β adrenergic receptor antagonists are combined. Similarly, it has been reported that administration of carvedilol, which is an αβ adrenergic receptor antagonist, inhibits the development of cardiac hypertrophy in SHR (35). It has been indicated that α1 adrenergic receptor blockers reduce the unfavorable effect of β blockers on insulin sensitivity and lipid metabolism (36).…”
Section: Analysis Of Monotherapy and Combination Therapy Of Adrenergimentioning
confidence: 96%
“…On the basis of previous reports, the degree of cardiovascular hypertrophy in SHR is not only governed by the level of blood pressure, but also by enhanced cellular responses to various growth factors such as angiotensin II (Dzau et al, 1991). Moreover, chronic fl-adrenoceptor antagonism has been reported either to reduce moderately (Lauva & Tomanek, 1985;Ohlstein et al, 1994) or not to affect heart weights in SHR (Chatelain et al, 1981). Nevertheless, morphological studies of the vasculature revealed that media smooth muscle hypertrophy of the mesenteric artery was significantly reduced by both of the present doses of celiprolol in SHR.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the antihypertrophic property of celiprolol may not be solely related to the haemodynamic changes induced by the treatment, and that other factors such as inhibition of neurohumoral activation or cellular growth may also be involved. Indeed it has been suggested that the antihypertrophic effect of carvedilol on vascular smooth muscle is mediated by a combination of haemodynamic and anti-mitogenic effects (Ohlstein et al, 1994). ACh relaxes arteries in an endothelium-dependent manner via the release of the endothelium-derived relaxing factor (EDRF), which stimulates smooth muscle soluble guanylate cyclase and elevates intracellular cyclic GMP (Moncada et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Carvedilol has been demonstrated to significantly reduce left ventricular and vascular hypertrophy in spontaneously hypertensive rats (74). The antihypertrophic property of carvedilol is partly independent of its antihypertensive effect.…”
Section: Antihypertrophic Actionmentioning
confidence: 99%